Continuous-Wave (CW) Photo-CIDNP NMR Spectroscopy A Tutorial - Kuhn, Lars T (Magnetic resonance in chemistry : MRC, 2025)
© 2025 The Author(s). Magnetic Resonance in Chemistry published by John Wiley & Sons Ltd.